Impact of lower limb elevation on blood pressure in cesarean patients: a quasi-experimental study - Suryanto Suryanto; Widigdo Rekso Negoro; Sindu Sintara; Annes Rindy Permana; Muhammad Rodli; Reko Priyonggo (International Journal of Public Health Science (IJPHS), 2026)
Among the available anesthetic techniques, spinal anesthesia remains the preferred method for cesarean section procedures, because of its rapid onset and safety profile; however, it is frequently associated with hypotension that may compromise maternal and fetal stability. This study was conducted to assess the influence of lower limb elevation as a non-pharmacological intervention on blood pressure following spinal anesthesia. A one-group pretest-posttest quasi-experimental design was implemented to evaluate 90 cesarean section patients who met the inclusion criteria. Blood pressure values, including systolic and diastolic parameters, were obtained at baseline and at the 5th, 10th, and 15th minutes after spinal anesthesia, and the data analysis using paired t-tests indicated significant increases in systolic and diastolic blood pressure over time, with mean systolic pressure rising from 87.59 mmHg to 97.89 mmHg and mean diastolic pressure increasing from 59.56 mmHg to 67.21 mmHg at minute 15 (p < 0.001). This study provides context-specific clinical evidence on the hemodynamic effects of lower limb elevation among post-spinal anesthesia cesarean section patients in a clinical setting. However, the non-inclusion of a control group and randomization reduce the strength of causal interpretation. These findings provide support for the notion that lower limb elevation may enhance potential benefits as a supportive intervention for post-spinal hypotension and warrant further controlled studies to confirm its efficacy.